Restoration-repair potential of resin-modified glass ionomer cement - Silva, Carolina Lopes da (2024)
Abstract: This in vitro study aimed to evaluate the repair bond strength of resin-modified glass ionomer cement using either the same material or a universal adhesive in the etch-and-rinse and self-etch modes plus resin composite. Twenty-four resin-modified glass ionomer cement blocks were stored in distilled water for 14 d and thermocycled. Sandpaper ground specimens were randomly assigned to three experimental groups according to the repair protocol: resin-modified glass ionomer cement (Riva Light Cure, SDI) and universal adhesive (Scotchbond Universal Adhesive, 3M Oral Care) in etch-and-rinse or self-etch modes and nanohybrid resin composite (Z350 XT, 3M Oral Care). After 24 h of water storage, the blocks were sectioned, and bonded sticks were subjected to the microtensile bond strength (μTBS) test. One-way ANOVA and Tukey’s test were used to analyze the data. The failure mode was descriptively analyzed. The highest μTBS values were obtained when the resin-modified glass ionomer cement was repaired using the same material (p < 0.01). In addition, the mode of application of the universal adhesive system did not influence the repair bond strength of the resin-modified glass ionomer cement. Adhesive/mixed failures prevailed in all groups. Repair of resin-modified glass ionomers with the same material appears to be the preferred option to improve bond strength.